Public prioritisation of energy affordability in the UK - Demski, Christina; Evensen, Darrick; Pidgeon, Nick; Spence, Alexa (Elsevier, 2017)
Much research has focused on the so-called ‘energy trilemma’ – i.e., three leading energy policy issues: energy security, affordability, and climate change mitigation. Whilst substantial understanding exists of why people support climate-friendly energy policies, little is known about why they think affordability is important. Particularly, what leads members of the public to identify this policy goal as more important than other objectives? Here, we examine this question via a nationally-representative survey of 2441 UK residents and demonstrate that concerns about personal costs explain a small amount of variation in the prioritisation of affordability as an energy policy goal; a range of other factors also significantly contribute. One such factor is beliefs about who is responsible for energy transitions. These findings suggest policy actions to address affordability concerns should go beyond energy prices, and include additional considerations such as distributive justice and equality.